Review of Human Resources Utilization by Utilizing Village Funds for Development in Bicak Village - Dharmawan, Faris Adi; Marini, Yushita (Accounting and Business Journal, 2022)
This research aims to analyze the utilization of human resources in the form of involvement of villagers by utilizing village funds for the development sector such as roads, irrigation, bridges and other infrastructure in Bicak Village whether they comply with statutory provisions or not. The analytical method used is a qualitative method with a literature study approach by collecting and studying written sources in both hardcopy and softcopy form such as e-books related to the topics discussed to obtain secondary data related to the topic as well as obtaining theoretical and legal basis to be used in the preparation of this scientific work and field studies through direct interaction with research objects. Collecting data by coming to the location object directly to obtain the necessary information which can be done by interviewing and collecting related documents for analysis purposes in writing objects. The results of the research show that not all human resource utilization activities for village development programs are in accordance with the provisions of laws and regulations. There were several construction activities that should have been completed in that fiscal year that had not yet been executed